2020
DOI: 10.1038/s41698-020-0123-0
|View full text |Cite
|
Sign up to set email alerts
|

Somatic copy number profiling from hepatocellular carcinoma circulating tumor cells

Abstract: Somatic copy number alterations (SCNAs) are important genetic drivers of many cancers. We investigated the feasibility of obtaining SCNA profiles from circulating tumor cells (CTCs) as a molecular liquid biopsy for hepatocellular carcinoma (HCC). CTCs from ten HCC patients underwent SCNA profiling. The Cancer Genome Atlas (TCGA) SCNA data were used to develop a cancer origin classification model, which was then evaluated for classifying 44 CTCs from multiple cancer types. Sequencing of 18 CTC samples (median: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…incorporated laser microdissection technology to isolate single CTCs for profiling somatic copy number alterations (SCNAs). There was an 80% concordance of SCNA profiling between HCC CTCs and primary tumors 62 . Sun et al .…”
Section: Circulating Tumor Cell Molecular Informationmentioning
confidence: 94%
See 1 more Smart Citation
“…incorporated laser microdissection technology to isolate single CTCs for profiling somatic copy number alterations (SCNAs). There was an 80% concordance of SCNA profiling between HCC CTCs and primary tumors 62 . Sun et al .…”
Section: Circulating Tumor Cell Molecular Informationmentioning
confidence: 94%
“…There was an 80% concordance of SCNA profiling between HCC CTCs and primary tumors. 62 Sun et al displayed that the CTCs purified by the latest NanoVelcro assay, that is, Click Chip, possessed highly concordant expression of 64 HCC tissue-derived genes from The Cancer Genome Atlas (TCGA). 14 Lee et al established a 10-gene HCC CTC Risk Score panel (DDR1, EHHADH, AR, LUM, HSD17B6, PMEPA1, TSKU, NECAB2, LAD1, and SLC27A5) quantified by the NanoString nCounter platform 65 and the risk score was significantly associated with overall survival.…”
Section: Circulating Tumor Cell Molecular Informationmentioning
confidence: 99%
“…Genetic analysis showed that CTCs derived from advanced-stage HCC tissues have HER-2 amplification and TP53 deletion. Using the Cancer Genome Atlas (TCGA)-based SCNA profiling, tumor tissue origination was confirmed for 73% of CTCs from 75% of cancer patients (71).…”
Section: Phenotyping and Genotyping Of Circulating Tumor Cellsmentioning
confidence: 99%
“…Importantly, sequencing studies exploring the genomic landscape of CTCs (Chemi et al 2019; Gulbahce et al 2017; Magbanua et al 2018; Court et al 2020) have shown that the mutational profiles of CTCs generally reflects the overall genomic composition of matched primary and metastatic lesions. Collectively, these results suggest that CTC diversity represents the overall tumor heterogeneity probably better than single tumor tissue biopsies, and incorporating CTC genomic information is expected to increase the clinical value of liquid biopsies by providing better predictions of therapeutic sensitivity and survival outcome (Pailler et al 2019; Paoletti et al 2018).…”
Section: Introductionmentioning
confidence: 99%